AB0420 Satisfaction and Unmet Need among Systemic Lupus Erythematosus (SLE) Patients Taking Standard of Care Medications (SOC) in A Real World Setting. (15th July 2016) - Ramachandran, S.; Pascoe, K.; Hoskin, B.; Lobosco, S.; Bell, D.; Pobiner, B.; Asukai, Y.
Abstract : Background: Limited data exists to assess drivers of treatment satisfaction and areas of unmet need among patients with SLE. Objectives: Primary: Assess physician and patient reported treatment satisfaction and unmet need amongst SOC patients treated ≥3 months. Secondary: Describe factors associated with satisfaction among SLE patients treated with SOC. SOC is defined as ≥1 of the following treatments: anti-malarials [AMs], corticosteroids, [CS] immunosuppressants [IMs] or non-steroidal anti-inflammatory drugs [NSAIDs]. Methods: Cross-sectional study of 88 US rheumatologists and their next five, SLE patients. Patient record forms (PRFs) were completed by physicians and patients provided data via self-completion forms (PSCs). Clinical burden, quality of life and satisfaction data were collected from both parties. Descriptive and bivariate analysis was used to profile SOC patients. Backwards stepwise logistic regression was used to assess drivers of physician and patient reported treatment satisfaction. Results: Rheumatologists provided 369 SOC PRFs; 228 corresponding PSCs were completed by SOC patients (mean age 44.0, majority female [86%], Caucasian [56%] and working/studying [63%]). Current SLE disease severity for a majority of SOC patients was described as mild by their physician, however 25% were described as moderate/severe. Current SLE status was described by physicians as deteriorating/unstable for 12% of SOC patients and physicians reported dissatisfaction with treatment in 18% (a figure matched by PSC patients). A significant correlation existed between decreased satisfaction (patient & physician) and increased disease severity (p<0.001) and/or deteriorating disease status (p<0.001). Significant associations with physician satisfaction were observed in the following covariates; musculoskeletal involvement (vs. no involvement) (OR: 0.05, p<0.001), disease status (deteriorating vs. improving/stable) (OR: 0.06, p<0.001), reduction in activities of daily living (ADLs) (vs. no reduction) (OR: 0.14, p<0.001), improvement in general symptomatology (vs. no improvement) (OR: 10.66, p<0.001). Significant associations with patient satisfaction were observed in the following covariates; Number of symptoms (OR per additional symptom: 0.88, p=0.020), reduction in ADLs (vs. no reduction) OR: 0.34, p=0.030, improvement in general symptomatology (vs. no improvement) (OR: 3.44, p=0.017), frequency of medication administration (satisfied vs. dissatisfied) (OR: 7.07, p<0.001). Conclusions: Clinical burden (disease severity/disease deterioration) continues to impact over a quarter of current patients on SOC. This burden has a significant bearing on both physician and patient satisfaction with treatment, particularly among moderate/severe & deteriorating patients. These findings are worthy of further exploration to ensure best clinical practice and ways to enhance physician and patient communication. Acknowledgement: Study (202146) funded by GSK Disclosure of Interest: S. Ramachandran Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, K. Pascoe Employee of: GlaxoSmithKline employee at time of the study, B. Hoskin Employee of: Adelphi Real World, S. Lobosco Employee of: Adelphi Real World, D. Bell Employee of: Adelphi Real World, B. Pobiner Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, Y. Asukai Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline